Violenzia : and other deadly amusements - Sala, Richard (Fantagraphics Books, 2015)
'Let there be no mercy or forgiveness for they have shown none.' With these words, whispered into the wind, a mysterious young woman leaps into action with wild abandon, twin automatics blazing. Is she a brave and reckless heroine taking on a monstrous evil? Or is she a deranged angel of death? One thing is clear: whether she is dropping from a high window into a crowd of red-robed fanatical cultists, or facing down a horde of psychotic hillbillies, you don't want to get in her way. Fast moving, Violenzia is a blast of pulpy fun, told in scenes of audacious action and splashes of rich watercolors. With elements of golden age comics and old movies mixed with Sala's trademark humor and sense of the absurd, Violenzia is a bloody enigma masked as eye candy, a puzzle box riddled with bullet holes from comics' master of the macabre. Full color illustrations throughout." --